Functional Neurological Recovery after Multiplace Hyperbaric Oxygen Therapy in Chronic Hemorrhagic Stroke Secondary to Rupture of a Cerebral Arteriovenous Malformation: A Case Report - Fogliene, Walmir; Zavarezzi, Antônio; Durigan, Silmara Rodrigues; Lima, Leandro Bueno (Brazilian Journal of Case Reports, 2026)
Hemorrhagic stroke resulting from the rupture of a cerebral arteriovenous malformation is associated with high morbidity and often leads to severe and persistent neurological deficits. Traditionally, the potential for functional recovery is considered to decline significantly after the subacute phase of the cerebrovascular event. However, recent evidence suggests that hyperbaric oxygen therapy may stimulate neuroplasticity processes and promote functional recovery even in the early chronic phase. This case report describes the clinical course of a previously healthy patient who developed a hemorrhagic stroke secondary to rupture of an arteriovenous malformation in the left hemisphere, evolving with right-sided hemiplegia and severe expressive aphasia following emergency neurosurgical treatment. Approximately eight months after the initial event, a therapeutic protocol consisting of fifty sessions of hyperbaric oxygen therapy in a multiplace chamber was initiated, with administration of one hundred percent oxygen at pressures above atmospheric levels. During treatment, progressive improvement in motor function and verbal communication was observed, with significant gains in muscle strength and increased language fluency. Clinical reassessment demonstrated relevant functional recovery and maintenance of neurological gains after completion of therapy. This case highlights the potential of hyperbaric oxygen therapy as an adjunctive strategy in neurological rehabilitation during the chronic phase following severe stroke.